Equicevian points and equiangular lines of a triangle in an isotropic plane - Kolar-Begović, Zdenka; Kolar-Šuper, Ružica; Volenec, Vladimir (Sarajevo Journal of Mathematics, 2015)
The concepts of equicevian points and equiangular lines of a triangle in an isotropic plane are studied in this paper. A number of significant properties of the introduced concepts are considered.